Analisis Klaster Kabupaten dan Kota di Kalimantan Selatan untuk Penentuan Kota Inflasi Acuan - Ahmadi Murjani; Awang Pramila; Aris Rusyiana (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2022)
The dynamic of the economy causes a price change in trade. The calculation of the overall price changes becomes essential in economic control to create a better welfare distribution. To date, regencies and municipalities that have not been included in the process of the inflation calculation, refer to the nearest city of inflation. It needs research as input to determine the next additional city of inflation as well as to set the reference city of inflation, to make the price controlling policy more accurate based on the characteristics of the regions. However, research on the referencing city of inflation is limited. Based on the BPS of South Kalimantan data, this research utilizes the quantitative method to create clusters of regencies and municipalities in South Kalimantan. The clustering process aims to re-mapping the regencies and municipalities in South Kalimantan based on the similar characteristics of macro variables that affecting inflation referring to the existing three cities of inflation (Banjarmasin, Tanjung, and Kotabaru). Based on the Hierarchical Clustering method, this research found that there are three main clusters in South Kalimantan covering the region of cities, the region of mineral mining, and the underdeveloped region. Also, in the period from 2010 to 2020, there are the dynamics of the clustering process.